Analysis of Readability of Non-Literary Texts in Thematic Books for Students of Class VI SD/MI Semester 1 Revised 2018 Based on SMOG Criteria - Effendi, Muhammad Yusuf; Arafik, Muh; Rini, Titis Angga (Journal of Education for Sustainability and Diversity, 2024)
The degree of readability serves as a gauge for how difficult it is to understand a text. Its meaning is usually expressed in the form of age or class rank. The standard level of assessment in the SMOG test on the text is in terms of the number of sentences that make up the text and the amount of vocabulary that has 3 or more syllables in the text. This study uses a content analysis research design on buku teks tematik siswa kelas VI SD/MI edisi revisi tahun 2018 Kementerian Pendidikan dan Kebudayaan, to find out the level of readability of non-literary texts in the book and their suitability for sixth grade of elementary school students based on SMOG criteria. The results showed that the thematic textbooks for sixth grade elementary school students in semester 1 of the 2018 revision contained 6 non-literary texts that matched the readability level of sixth grade elementary school students and 19 non-literary texts that did not match the readability level of sixth grade elementary school students.